Indonesian Migrant Worker Learning Communities in Taiwan: It is Not Only Online Learning, It is Our Gathering - Suryaneta Suryaneta; Yuherina Gusman (Ideas Publishing, 2022)
This research purported to gain a more thoughtful and insightful understanding of female Indonesian migrant workers’ perceptions and experiences on online learning in Taiwan. To achieve this research purpose, researchers collected qualitative data from a series of in-depth interviews with five participants who joined online learning in community learning through one of Taiwan’s largest women religious NGOs, Salimah Taiwan. The Interpretative Phenomenological Analysis was purposely selected to analyze the data to draw the participants’ lived experiences during online learning. The five significant theme findings were intrinsically interwoven and pivotal to adult learning, especially in the context of online learning. Penelitian ini dimaksudkan untuk mendapatkan pemahaman yang lebih mendalam dan bermakna tentang persepsi dan pengalaman pekerja migran perempuan Indonesia tentang pembelajaran daring di Taiwan. Untuk mencapai tujuan penelitian ini, peneliti mengumpulkan data kualitatif dari serangkaian wawancara mendalam dengan lima peserta yang mengikuti pembelajaran daring dalam pembelajaran komunitas melalui salah satu LSM keagamaan wanita terbesar di Taiwan, Salimah Taiwan. Interpretative Phenomenological Analysis sengaja dipilih untuk menganalisis data guna menarik pengalaman hidup peserta selama proses pembelajaran. Lima temuan tema yang signifikan secara intrinsik terjalin dan penting untuk pembelajaran orang dewasa, terutama dalam konteks pembelajaran daring.